2022
DOI: 10.1007/s11104-022-05335-2
|View full text |Cite|
|
Sign up to set email alerts
|

Revealing the underlying mechanisms mediated by endophytic actinobacteria to enhance the rhizobia - chickpea (Cicer arietinum L.) symbiosis

Abstract: Purpose The effects of endophytic actinobacterial strains, Microbispora sp. CP56, Actinomadura sp. CP84B, Streptomyces spp. CP200B and CP21A, on the chickpea-Mesorhizobium symbiosis, were investigated in planta, with the aim of revealing the underlying mechanisms of action. Methods The actinobacterial endophytes were co-inoculated with Mesorhizobium ciceri onto chickpea seedlings to study the effect on plant growth parameters, nodulation development and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 72 publications
1
6
0
Order By: Relevance
“…differs in its morphological traits on various medium (Figure 1 A-B), which is consistent with past observations (8). Changes in the isolate's phenotype show that variation in the composition of media influence the primary and secondary metabolism (14) . Light microscopic observation revealed that the strain is polysporous with branched mycelium.…”
Section: Cultural and Morphological Characterizationsupporting
confidence: 91%
See 1 more Smart Citation
“…differs in its morphological traits on various medium (Figure 1 A-B), which is consistent with past observations (8). Changes in the isolate's phenotype show that variation in the composition of media influence the primary and secondary metabolism (14) . Light microscopic observation revealed that the strain is polysporous with branched mycelium.…”
Section: Cultural and Morphological Characterizationsupporting
confidence: 91%
“…Presence of Streptomyces sp. as an endophyte could be a symbiotic association, since they produce bioactive compounds which exert beneficial functions for plant growth and protection in return the host plant allows the survival of these microorganisms (14) .…”
Section: Isolation Of Endophytic Actinobacteriamentioning
confidence: 99%
“…The authors consider the consortium to be a potential biofertilizer for promoting sustainable agriculture. Co-inoculation of actinobacterial endophytes isolated from chickpea roots with M. ciceri increased total plant N and approximately 30% of shoot biomass [ 155 , 156 ]. Exudates from chickpea roots colonized by actinobacteria stimulate nodulation-related biological processes and may help improve chickpea production under field conditions.…”
Section: Pgpr Benefits: Nutrition Enhancement and Tolerance To Abioti...mentioning
confidence: 99%
“…CP84B, Streptomyces spp. CP200B, and CP21A with Mesorhizobium cicero in chickpea seedlings showed growth promotion and enhancement of the rhizobia–chickpea symbiosis by increasing nodulation-related biological processes such as rhizobial chemotaxis, biofilm formation, and nod gene expression [ 74 ]. When PGP endophytic strains Microbispora sp.…”
Section: Actinobacteria Diversity Associated With Plants and Plant Gr...mentioning
confidence: 99%